"Simple Methods to Derive Primary Malignant Glioma Cell Lines and Assay of Cellular Damage for Preclinical Studies". (7th February 2018) - Thakur, Kalyani; Shyam, Sai; George, Jennifer; A. G., Shobha; Rao, K. V. L. Narasinga; Kalia, Vijay Kumar
ABSTRACT: Primary malignant glioma cell lines are being used for initial screening of anticancer agents. We utilized a simple mechanical disaggregation method for deriving cell lines from tumor tissues; and a Coverslip Culture-Acridine Orange Staining method to study cellular damage. Cell lines could be grown for up to three passages within three weeks after surgery. Cell proliferation, total cellular damage, and MTT assay were studied as parameters of cytotoxic response. Frequencies of damaged cells varied in different cell lines; and increased after cytotoxic treatments under clinically relevant conditions. These methods could contribute to preclinical evaluation of treatment response before commencement of radio-chemotherapy.